MMHD [(S,E)-2-Methyl-1-(2-methylthiazol-4-yl) hexa-1,5-dien-ol], a Novel Synthetic Compound Derived From Epothilone, Suppresses Nuclear Factor-κB-Mediated Cytokine Expression in Lipopolysaccharide-Stimulated BV-2 Microglia - Na-Ra Jeon; Sushruta Koppula; Byung-Wook Kim; Su-Ho Park; Hyo-Won Lee; Dong-Kug Choi (Elsevier, 2010)
The effects of MMHD [(S,E)-2-methyl-1-(2-methylthiazol-4-yl) hexa-1,5-dien-ol], a novel synthetic compound derived from epothilone, was investigated for its effects on the expression of proinflammatory mediators in lipopolysaccharide-stimulated BV-2 microglia. MMHD attenuated the expressions of inducible nitric oxide synthase and cyclooxygenase-2 mRNA and protein without affecting cell viability. Moreover, MMHD suppressed nuclear factor-κB (NF-κB) activation via the translocation of p65 into the nucleus. These results indicate that MMHD exerts anti-inflammatory properties by suppressing the transcription of proinflammatory cytokine genes through the NF-κB signaling pathway. Keywords:: microglia, lipopolysaccharide, nuclear factor-κB (NF-κB), MMHD [(S,E)-2-methyl-1-(2-methylthiazol-4-yl) hexa-1,5-dien-ol], neurodegenerative disease